Integrated Transcriptomic Analysis Reveals a Distinctive Role of YAP1 in Extramedullary Invasion and Therapeutic Sensitivity of Multiple Myeloma - Zheng, Bo; Sun, Wei; Yi, Ke; Zhang, Yajun; Wang, Liangzhe; Lan, Hongyan; Zhang, Chong; Xian, Hongming; Li, Rong (Frontiers in Oncology, 2022)
Multiple myeloma(MM) is the second most common hematologic malignancy. There is no standard therapeutic guidelines for extramedullary invasion(EM). We performed a retrospective integrated transcriptomic analysis based on GEO, TCGA, Oncomine datasets with a toal of over 2500 cases enrolled. GSVA analysis was performed on GSE24080. The external validation cohorts include GSE9782, GSE2658, MMRF-COMPASS and Oncomine. The data of MGUS to replased MM was acquired from GSE6477, GSE5900 and Oncomine. The data of EM was acquired from GSE39683 and GSE66291. Single-cell level transcriptome data of MM and EM was acquired from GSE106218. GSVA analysis revealed that 559 cases could be divided into 2 groups based on the expression of oncogenic pathways with prognostic significances. Group 1 with a specific phenotype of YAP1-MYC+ exhibited an unpromising prognosis. The univariate analysis revealed YAP1 as a tumor suppressor in MM. The activity of DNA repair, glycolysis and oxidative phosphorylation were significantly higher in YAP1-MYC+ MM which is in concordance with EM myeloma cells based on single-cell analysis. Furthermore, we discovered YAP1-MYC+ MM patients exhibited an improved response for IMiD treatment. Collectively, YAP1-MYC+MM patients might suffer a worse prognosis and stronger propensity for EM progression.